Analisis Pengaruh Risiko Kredit dan Risiko Operasional terhadap Profitabilitas Bank Umum BUMN yang Terdaftar di BEI untuk Periode 2021–2022 - Dina, Dina Anggraeni Susesti; Mohammad Ghofirin (Universitas Nahdlatul Ulama Surabaya, 2023)
The global economy is still having an impact on the banking industry. Financial and monetary conditions this year are better than the previous year. Several domestic factors support the expansion of the banking industry. The aim of this research is to see the influence of credit risk and operational risk on profitability in state-owned commercial banks listed on the IDX for the 20212022 period. This research method is multiple linear regression, using tools in the form of SPSS software. The results of this research show that credit risk and operational risk simultaneously influence profitability for state-owned commercial banks registered on the IDX in the 2021-2022 period, partially using Return on Assets (ROA).